Dietary Vitamins A, C, and Potassium Intake Is Associated With Narrower Retinal Venular Caliber - Edo, Ayaka; Ibrahim, Diah Gemala; Hirooka, Kazuyuki; Toda, Rie; Kamaruddin, Muhammad Irfan; Kawano, Reo; Nagao, Akiko; Ohno, Haruya; Yoneda, Masayasu; Kiuchi, Yoshiaki (Frontiers in Medicine, 2022)
Introduction: The retinal vasculature, a surrogate for the systemic microvasculature, can be observed non-invasively, providing an opportunity to examine the effects of modifiable factors, such as nutrient intake, on microcirculation. We aimed to investigate the possible associations of dietary nutrient intake with the retinal vessel caliber. Methods: In this cross-sectional study, a total of 584 participants in a medical survey of Japanese de-scendants living in Los Angeles in 2015 underwent a dietary assessment, fundus photographic examination, and comprehensive physical and blood examinations. Retinal vessel caliber was measured using fundus photographs with a semi-automated computer system and summarized as central retinal artery and vein equivalents (CRAE and CRVE). The association between dietary nutrient intake and retinal vessel caliber was analyzed using a multivariate linear regression model adjusted for two models including potential confounders. The first model was adjusted for age and sex. The second model was adjusted for age, sex, smoking status, body mass index (BMI), hypertension, diabetes, dyslipidemia, history of coronary heart disease (CHD), and history of stroke. Results: After adjustment of potential confounders, compared to the quartile with the lowest intake, the difference in CRVE for the highest quartile was −5.33m (95% confidence interval [CI]: −9.91 to −0.76, P for trend = 0.02) for vitamin A, −4.93m (95% CI: −9.54 to −0.32, P for trend = 0.02) for vitamin C and −3.90m (95% CI: −8.48 to 0.69, P for trend = 0.04) for potassium. Conclusions: A significant association was observed between higher vitamins A, C and potassium intakes and narrower retinal venular caliber.